A Nanopore Phosphorylation Sensor for Single Oligonucleotides and Peptides - Yi-Lun Ying; Jie Yang; Fu-Na Meng; Shuang Li; Meng-Ying Li; Yi-Tao Long (Research, 2019)
The phosphorylation of oligonucleotides and peptides plays a critical role in regulating virtually all cellular processes. To fully understand these complex and fundamental regulatory pathways, the cellular phosphorylate changes of both oligonucleotides and peptides should be simultaneously identified and characterized. Here, we demonstrated a single-molecule, high-throughput, label-free, general, and one-step aerolysin nanopore method to comprehensively evaluate the phosphorylation of both oligonucleotide and peptide substrates. By virtue of electrochemically confined effects in aerolysin, our results show that the phosphorylation accelerates the traversing speed of a negatively charged substrate for about hundreds of time while significantly enhances the translocation frequency of a positively charged substrate. Thereby, the kinase/phosphatase activity could be directly measured with the aerolysin nanopore from the characteristically dose-dependent event frequency of the substrates. By using this straightforward approach, a model T4 oligonucleotide kinase (PNK) further achieved the nanopore evaluation of its phosphatase activity and real-time monitoring of its phosphatase-catalyzed dephosphorylation at a single-molecule level. Our study provides a step forward to nanopore enzymology for analyzing the phosphorylation of both oligonucleotides and peptides with significant feasibility in fundamental biochemical researches, clinical diagnosis, and kinase/phosphatase-targeted drug discovery.